Investigation on the Compressibility Factor of Hydrogen-Doped Natural Gas Using GERG-2008 Equation of State - Ji-Chao Li; Yong Fan; Dan Pang; Tong Wu; Ying Zhang; Ke Zhou (Energies)
The primary methods for hydrogen transportation include gaseous storage and transport, liquid hydrogen storage, and transport via organic liquid carriers. Among these, pipeline transportation offers the lowest cost and the greatest potential for large-scale, long-distance transport. Although the construction and operation costs of dedicated hydrogen pipelines are relatively high, blending hydrogen into existing natural gas networks presents a viable alternative. This approach allows hydrogen to be transported to the end-users, where it can be either separated for use or directly combusted, thereby reducing hydrogen transport costs. This study, based on the GERG-2008 equation of state, conducts experimental tests on the compressibility factor of hydrogen-doped natural gas mixtures across a temperature range of −10 °C to 110 °C and a pressure range of 2 to 12 MPa, with hydrogen blending ratios of 5%, 10%, 20%, 30%, and 40%. The results indicate that the hydrogen blending ratio, temperature, and pressure significantly affect the compressibility factor, particularly under low-temperature and high-pressure conditions, where an increase in the hydrogen blending ratio leads to a notable rise in the compressibility factor. These findings have substantial implications for the practical design of hydrogen-enriched natural gas pipelines, as changes in the compressibility factor directly impact pipeline operational parameters, compressor characteristics, and other system performance aspects. Specifically, the introduction of hydrogen alters the compressibility factor of the transported medium, thereby affecting the pipeline’s flowability and compressibility, which are crucial for optimizing and applying the performance of hydrogen-enriched natural gas in transportation channels. The research outcomes provide valuable insights for understanding combustion reactions, adjusting pipeline operational parameters, and compressor performance characteristics, facilitating more precise decision-making in the design and operation of hydrogen-enriched natural gas pipelines.